Assessing the effects of socioeconomic status on use of hypertension care services in Zambia: Insights from 2017 WHO stepwise survey - Flata Mwale; Wingston Felix Ng’ambi; Joe Maganga Zonda; Joseph Mfutso-Bengo; Dominic Nkhoma (International Journal of Noncommunicable Diseases, 2025)
Background: Hypertension remains a significant public health concern, with disparities in care delivery and inadequate healthcare infrastructure exacerbating its burden, particularly among underprivileged groups. However, evidence on the influence of socioeconomic factors on hypertension care utilization to inform tailored interventions to address these inequities remains limited in many low- and middle-income countries. This study aimed to investigate the impact of socioeconomic factors, including income and education, on the utilization of hypertension care services in Zambia. Methods: The study is based on nationally representative, cross-sectional, population-based survey data from 4,302 participants aged 18–69 years that participated in the Zambia’s 2017 WHO Stepwise Survey (STEPS). The primary outcome variable explored in the study was hypertension services utilization, and the key socioeconomic status (SES) determinants included income and education. The study also controlled for other confounding sociodemographic variables such as sex, age, body mass index, and behavioral risk factors. A probit regression model was employed to investigate the impact of SES on the likelihood of utilizing hypertension care services in Zambia in 2017. Results: Although the prevalence of hypertension was 18.7%, only 58.5% of individuals who were aware of their condition sought treatment, and 52% of respondents reported using at least one hypertension care service. The wealth quintile analysis revealed that the prevalence of hypertension was significantly higher among individuals in the medium, rich, and richest income groups, with probabilities 9.8%, 4.8%, and 6.7% higher, respectively, compared to those in their poorest counterparts. While education had no discernible effect on the prevalence of hypertension, it positively influenced service utilization. Specifically, participants with secondary and post-secondary education were 10.7% and 21.8% more likely, respectively, to use hypertension care services. In addition, while there were no notable differences in the prevalence or service utilization among individuals with elevated blood pressure, urban residents were 9.3% more likely to use hypertension services than their rural counterparts. Conclusion: Low service utilization and limited access to care, particularly among individuals with known hypertension, highlight the ongoing public health concern posed by the prevalence of hypertension. This underscores the urgent need for enhanced health system awareness and responsiveness. Targeted interventions are necessary to address inequalities stemming from socioeconomic and demographic disparities, including higher frequency in wealthier groups, improved service use among individuals with higher education, and increased utilization in urban areas.